Gender representation in leadership & research: a 13-year review of the Annual Canadian Society of Otolaryngology Meetings - Grace Yi; Jennifer Payandeh; Dorsa Mavedatnia; Penelope Neocleous; Jacob Davidson; Jennifer Siu; Molly Zirkle; Julie E. Strychowsky; M. Elise Graham; Yvonne Chan (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The gender disparity in surgical disciplines, specifically in speakers across North American medical and surgical specialty conferences, has been highlighted in recent literature. Improving gender diversity at society meetings and panels may provide many benefits. Our aim was to determine the state of gender diversity amongst presenters and speakers at the annual Canadian Society of Otolaryngology-Head and Neck Surgery (CSO) meetings. Methods Scientific programs for the CSO annual meetings from 2008 to 2020 were obtained from the national society website. Participant name, role, gender, location, and subspecialty topic were recorded for all roles other than poster presenter. Gender (male or female) was determined using an online search. The total number of opportunity spots and proportion of women was then calculated. Gender differences were analyzed using chi-square test and logistic regression with odds ratios. Four categories were analyzed: Society Leadership, Invited Speaker Opportunities, Workshop Composition (male-only panels or “manels”, female-only panels, or with at least one female speaker), and Oral Paper Presenters (first authors). Results There were 1874 leadership opportunity spots from 2008 to 2020, of which 18.6% were filled by women. Among elected leadership positions in the society, only 92 unique women filled 738 leadership opportunity spots. 13.2% of workshop chairs, 20.8% of panelists and 22.7% of paper session chairs were female. There was an overall increase in the proportion of leadership positions held by women, from 13.9% of leadership spots in 2008 to 30.1% in 2020. Of the 368 workshops, 61.1% were led by men only, 36.4% by at least 1 female surgeon, and 2.5% by women only. “Manels” have comprised at least 37.5% of workshops each year. Conclusions The proportion of women in speaking roles at the annual CSO meetings has generally increased over time, particularly among panelists, leading to fewer male-only speaking panels. However, there has been a slower rate of growth in the proportion of unique women in speaker roles. There remains an opportunity to increase gender/sex diversity at the major Canadian otolaryngology meeting. Graphical Abstract